Posterior arch anomalies of Atlas and its clinical significance - Umesh Kumar Mehta; Geetha K N; Mrinalini Gaikward; Lalita Chavan (International Journal of Medical Research and Review, 2014)
Introduction: Congenital anomalies of posterior arch of atlas are very rare. Most of the time detection of this developmental anomaly is incidental while investigating for neck pain and stiffness or injury involving the region of head and neck.Aim: Our aim was to determine the incidence of posterior arch anomaly of atlas in Maharashtra region. 75 dried human atlas vertebrae were included for this study.Observations: We detected Type A and B in our study.Results: The incidence of posterior arch anomaly is 4% i.e. 3 out of 75 vertebrae. We detected Type A and B in our study and these types are generally asymptomatic. Type C to E may be associated with neurological deficit.Conclusion: It is essential for the clinicians to recognize the condition and the specific type of anomaly in order to distinguish it from fractures secondary to trauma and for the proper guidance of the patients accordingly.